Iconography of a Stela of a Roman Centurion from the Archaeological Museum Zadar (Archaeologia Adriatica, 2014)
The paper discusses the iconography of the bottom part of a stela of a Roman centurion, kept at the Archaeological Museum Zadar and almost certainly originating from Burnum. The plate shows military awards (torques, a wreath, armillae and phalerae) and typical elements of the military equipment of a centurion: a vitis and greaves. The presentations in the set’s three upper phalerae display a particular uniqueness, size and quality of workmanship. Undoubtedly the left phalera represents a portrait bust.
Keywords: stela; centurion; dona militaria; phalerae; busts; portrait